The Effectiveness of The Coaching Program in State Prisons in Improving the Skills and Behavior of Inmates and Its Impact on Recidivism Rates - Ndalo, Antonius Axl Alot; Wilhelmus, Bhisa Vitus; Amalo, Heryanto (Faculty of Law, Universitas Pattimura, 2026)
Introduction: Recidivism remains a critical challenge in Indonesia's criminal justice system, particularly in correctional institutions like the Class IIB Ruteng Detention Center (Rutan). Purposes of the Research: This study analyzes the effectiveness of coaching programs in enhancing inmates' skills and behavior, and their impact on recidivism rates. Methods of the Research: Using an empirical juridical approach, primary data were collected through interviews with 20 inmates, 6 staff members, and observations at Rutan Ruteng, supplemented by secondary data from regulations and reports. Findings of the Research: Findings reveal that while personality and independence coaching programs (e.g., religious awareness, vocational training in woodworking and farming) show moderate effectiveness in skill improvement (70% participation rate), behavioral changes are inconsistent due to limited resources and external stigma. Recidivism averaged 3 inmates annually (2021-2024), primarily theft cases, indicating partial program impact. The study recommends enhanced funding, community partnerships, and post-release support to reduce recidivism below national averages (3.55% in 2023). This research contributes to correctional policy reform aligned with Law No. 22/2022 on Correctional System.